2023
DOI: 10.1021/acs.jchemed.2c01113
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality as a Medium of Asynchronous Content Delivery for Teaching about Enzymes

Abstract: Self-study is an integral part of chemistry learning, whereby the students consume knowledge outside of the classroom environment. The COVID-19 pandemic magnified the need for efficient methods of synchronous and asynchronous instructional content delivery worldwide. Virtual reality (VR) presents a prospective technological solution to aid asynchronous content delivery, particularly for visual subjects such as chemistry. We investigate the feasibility of using carefully designed VR-based content to assist offl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Several chemistry VRLEs allow users to physically reach and grab molecules, ,,,,, providing a bridge to the submicroscopic world and making molecules tangible, interactable, and dynamic (for additional VRLE examples, see Tables S6–S11). By taking advantage of behavior consistency, environment display, environment control, and object manipulation (see Table ), VRLEs can exceed the bounds of physical reality and allow developers to create worlds where the laws of space and time can be broken …”
Section: Technology Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Several chemistry VRLEs allow users to physically reach and grab molecules, ,,,,, providing a bridge to the submicroscopic world and making molecules tangible, interactable, and dynamic (for additional VRLE examples, see Tables S6–S11). By taking advantage of behavior consistency, environment display, environment control, and object manipulation (see Table ), VRLEs can exceed the bounds of physical reality and allow developers to create worlds where the laws of space and time can be broken …”
Section: Technology Designmentioning
confidence: 99%
“…Synthesized from literature reviews, we identified 89 fully immersive virtual reality (VR) environments (between 2000 and 2023) detailing potential applications for teaching or learning chemistry. , Among the significant volume of VR tools developed over the past two decades, only 26 of them mention educational frameworks as the foundation for their design, development, and/or assessment (see refs , , , , , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 VR can provide users with immersive, highly specialised training simulations, which have been shown to enhance engagement with learning materials and improve knowledge retention. [2][3][4][5][6][7] The applications of VR within scientific education have been many, allowing students to gain a deeper understanding of complex scientific concepts by way of visualisation, 8 such as within molecular visualisation. [9][10][11][12][13][14] Additionally, VR has excelled as a way of providing occupational training programs such as training in virtual organic synthesis laboratories, [15][16][17][18] and training for medical students across a large spectrum covering both clinical operations and medical procedures, to patient care.…”
Section: Introductionmentioning
confidence: 99%